2022
DOI: 10.3389/fimmu.2022.915709
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis and Single-Cell Sequencing Analysis Constructed the Ubiquitination-Related Signature in Glioma and Identified USP4 as a Novel Biomarker

Abstract: BackgroundGlioma, the most frequent malignant tumor of the neurological system, has a poor prognosis and treatment problems. Glioma’s tumor microenvironment is also little known.MethodsWe downloaded glioma data from the TCGA database. The patients in the TCGA database were split into two groups, one for training and the other for validation. The ubiquitination genes were then evaluated in glioma using COX and Lasso regression to create a ubiquitination-related signature. We assessed the signature’s predictive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
1
12
0
1
Order By: Relevance
“…An association study between risk ratings and immune cells showed that many immune cells were closely associated with risk scores. Lastly, high-risk BC patients showed higher expression levels of immune checkpoint genes than low-risk BC patients ( Tang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 97%
“…An association study between risk ratings and immune cells showed that many immune cells were closely associated with risk scores. Lastly, high-risk BC patients showed higher expression levels of immune checkpoint genes than low-risk BC patients ( Tang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 97%
“…Various signatures based on multiple marker genes have been established in gliomas. [37][38][39] However, these existing sig- showed average performance in other datasets. 24,40 This could be due to overfitting, resulting in poor generalization of the models.…”
Section: Discussionmentioning
confidence: 93%
“…For example, proteasomal inhibitors that block the ubiquitin-proteasome pathway have been approved and used effectively in clinical trials for the treatment of multiple myeloma [34]. Previous studies have also established ubiquitin-related signatures for other cancer types such as lung adenocarcinoma, hepatocellular carcinoma, and glioma [35][36][37][38]. Hence, we developed a novel gene expression signature based on a screen on a collection of UbRGs and determined its prognostic significance in OV (Figures 2 and 3).…”
Section: Advances Of the Ubrgs Signature For Prognostic Prediction In Ovmentioning
confidence: 99%